Odpowiedzi

Najlepsza Odpowiedź!
2010-03-09T18:15:12+01:00
B)2x-3/4=1/2+x
2x-x=1/2+3/4
x=5/4
c)x+2/9+x-1/3=1
2x=1-2/9+1/3
2x=9/9-2/9+3/9
2x=10/9
x=5/9
d)2x+3/5=2-x/3+x
2x+x/3-x=-3/5+2
4x/3=7/5
4x=21/5
x=21/20
e)3x-5/2-5x-1/10=0
-2x=5/2+1/10
-2x=25/10+1/10
-2x=26/10
2x=-26/10
x=-26/20
x=-1,3
f)x/2=2/5(4-x)-4
x/2=8/5-2/5x-4
x/2+2/5x=8/5-4
5x/10+4x/10=8/5-20/5
9x/10=-14/5
9x=-140/5
9x=-28
x=-28/9
g)2x-1/5-x-2/2=0,7x
2x-x-0,7x=1/5+1
0,3x=6/5
3/10x=6/5
3x=60/5
x=60/15
x=4
h)2x-3x+5/4=-1/4x-1
2x-3x+1/4x=-5/4+1
-3x/4=-1/4
-3x=-1
x=1/3
2010-03-09T18:17:20+01:00
B)2x-3/4=1/2+x
x=1/2+3/4
x=5/4

c)x+2/9+x-1/3=1
2x=1-2/9+1/3
2x=10/9
x=5/9

d)2x+3/5=2-x/3+x
2x+1/3x-x=2-3/5
4/3x=7/5
x=21/20

e)3x-5/2-5x-1/10=0
-2x=26/10
x=-13/10

f)x/2=2/5(4-x)-4
1/2x=8/5-2/5x-4
1/2x+2/5x=8/5-4
9/10x=-12/5
x=-8/3

g)2x-1/5-x-2/2=0,7x
x-0,7x=6/5
3/10x=6/5
x=4

h)2x-3x+5/4=-1/4x-1
-x+1/4x=-1-5/4
-3/4x=-9/4
x=3
2010-03-09T18:29:18+01:00
B. 2x-3/4=1/2+x
2x-x=3/4+1/2
x=1/4+2/4
x=3/4

c.x+2/9+x-1/3=1
x+x=-2/9+1/3+1
2x=10/9:2x
x=5/9

e.3x-5/2-5x-1/10=0
3x-5x=5/2+1/10
-2x=25/10+1/10
-2x=26/10:(-2)
x=-13/10

g.2x-1/5-x-2/2=0,7x
2x-x-0,7x=1/5+1
-0,3x=6/5:(-0,3)
x=-4

h. 2x-3x+5/4=-1/4x-1
2x-3x+1/4x=-5/4-1
-x+1/4x=-9/4
-3/4x=-9/4:(-3/4)
x=3